Cardiac muscle organization revealed in 3-D by imaging whole-mount mouse hearts using two-photon fluorescence and confocal microscopy. (November 2015) - Sivaguru, Mayandi; Fried, Glenn; Sivaguru, Barghav S.; Sivaguru, Vignesh A.; Lu, Xiaochen; Choi, Kyung Hwa; Saif, M Taher A; Lin, Brian; Sadayappan, Sakthivel
The ability to image the entire adult mouse heart at high resolution in 3-D would provide enormous advantages in the study of heart disease. However, a technique for imaging nuclear/cellular detail as well as the overall structure of the entire heart in 3-D with minimal effort is lacking. To solve this problem, we modified the benzyl alcohol:benzyl benzoate (BABB) clearing technique by labeling mouse hearts with periodic acid Schiff (PAS) stain. We then imaged the hearts with a combination of two-photon fluorescence microscopy and automated tile-scan imaging/stitching. Utilizing the differential spectral properties of PAS, we could identify muscle and nuclear compartments in the heart. We were also able to visualize the differences between a 3-month-old normal mouse heart and a mouse heart that had undergone heart failure due to the expression of cardiac myosin binding protein-C ( cMyBP-C ) gene mutation (t/t). Using 2-D and 3-D morphometric analysis, we found that the t/t heart had anomalous ventricular shape, volume, and wall thickness, as well as a disrupted sarcomere pattern. We further validated our approach using decellularized hearts that had been cultured with 3T3 fibroblasts, which were tracked using a nuclear label. We were able to detect the 3T3 cells inside the decellularized intact heart tissue, achieving nuclear/cellular resolution in 3-D. The combination of labeling, clearing, and two-photon microscopy together with tiling eliminates laborious and time-consuming physical sectioning, alignment, and 3-D reconstruction.